The point-slope equation is the following:
![y-y_1=m(x-x_1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/csobd57zth7rh9k4hz9amldzpq2owf0z4j.png)
Where (x1, y1) is a point of the line and m is the slope.
The slope is calculated as:
![m=(y_2-y_1)/(x_2-x_1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/78uaqhwt0aws3qfwxigaftpihnmb1gzxtp.png)
Where (x1, y1) and (x2, y2) are points of the line. So, replacing (x1, y1) by (-2, 6) and (x2, y2) by (5, 1), we get:
![m=(1-6)/(5-(-2))=(-5)/(5+2)=(-5)/(7)](https://img.qammunity.org/2023/formulas/mathematics/college/s8onf1dnwvhaufl2k3n29felkeo72ihw0f.png)
Then, the point-slope form is:
![\begin{gathered} y-6=(-5)/(7)(x-(-2)) \\ y-6=(-5)/(7)(x+2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/78jgu5d7mu72e2a6044visiuah39wvm3rd.png)
Finally, to rewrite the equation in slope-intercept form, we need to solve for y as:
![\begin{gathered} y-6=(-5)/(7)(x+2) \\ y-6=(-5)/(7)x+(-5\cdot2)/(7) \\ y-6=(-5x)/(7)-(10)/(7) \\ y=(-5x)/(7)-(10)/(7)+6 \\ y=(-5x)/(7)+(32)/(7) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/q7wa8l55bb7gkhsk84ci9xegdsgfcltvpw.png)
Answer: Point-slope form:
![y-6=(-5)/(7)(x+2)](https://img.qammunity.org/2023/formulas/mathematics/college/6eps9wy4y1uur5oxwur0zguubtegbqf1fq.png)
Slope-Intercept form:
![y=(-5)/(7)x+(32)/(7)](https://img.qammunity.org/2023/formulas/mathematics/college/7u8okejx9t2nvu9t9x1n58cqexm09imm59.png)